PTC engineering MathCAD worksheets. (Parametric Technology Corp., 2011)
The worksheets in this PTC collection can be used as templates for solving typical problems encountered in the structural design of buildings, heat transfer and thermal dynamics in buildings, electromagnetics, including transmission lines/Smith charts, power distribution problems, structural analysis and general boundary value problems. They are available in US Customary and Metric units and in Mathcad 14, 15 and Prime.